Pengaruh Addendum Formularium Rumah Sakit dan Kepatuhan Dokter dalam Penulisan Resep terhadap Efisiensi Persediaan Farmasi dengan Variabel Intervening Pengendalian Persediaan Farmasi - Lidwina Cahyadinata; Agusdini Banun Saptaningsih; Johanes Johanes (Pusat Riset dan Inovasi Nasional, 2025)
The efficiency of pharmaceutical inventory is aimed not only at cost reduction but also at ensuring the continuity of patient care. To achieve pharmaceutical inventory efficiency, pharmaceutical inventory control, hospital formulary addendums, and physician adherence are required. The objective of this study is to analyze the effect of hospital formulary addendums and physician adherence to formulary-based prescribing on pharmaceutical inventory efficiency, with inventory control as an intervening variable.This research is confirmatory in nature and uses a quantitative approach. The sample consists of secondary data derived from observations of patient prescriptions at BSH Hospital over a 28-month period, from January 2022 to April 2024. The F-test concluded that hospital formulary addendums, physician adherence to prescribing, and pharmaceutical inventory control simultaneously influence pharmaceutical inventory efficiency. Using SEM-PLS analysis, it was found that pharmaceutical inventory control has a significant effect on pharmaceutical inventory efficiency. Furthermore, SEM analysis via JASP (Jeffrey's Amazing Statistics Program) showed that physician adherence to formulary-based prescribing has a direct influence on pharmaceutical inventory efficiency and also an indirect influence through inventory control. In contrast, hospital formulary addendums in this study were not proven to have either a direct or indirect effect on pharmaceutical inventory efficiency through inventory control.